A reputation-oriented trust model for multi-agent environments. Issue 7 (8th August 2016) - Majd, Elham; Balakrishnan, Vimala
Abstract : Purpose: This paper aims to enhance trust in multi-agent systems by presenting a new computational model, named R-D-C (Reputation-Distribute-Conflict), to select the most trustworthy provider agent based on computing reputation, disrepute, and conflict of each provider agent. Design/methodology/approach: R-D-C propose based on three vital components for evaluating trustworthiness of providers as reputation, disrepute, and conflict, where disrepute is a component almost all trust models ignored. The R-D-C model presents a computational method for evaluating to select the most trustworthy provider agent. In order to evaluate the R-D-C model, the experimentation was carried out in two stages, by designing a simulated multi-agent environment. First, the accuracy of the R-D-C model in computing reputation, disrepute, and conflict was investigated. Second, the performance of the model was compared with other existing trust models. Moreover, comparison of the performance of the R-D-C model with other models demonstrates that the R-D-C model performs significantly better than the other models. Therefore, the R-D-C model is capable of evaluating the trustworthiness of agents more accurately and it can select the most trustworthy provider better than the other models. Findings: The results show that the R-D-C model works well in different multi-agent environments, even when the number of untrustworthy providers is higher than that of the trustworthy ones. Originality/value: The R-D-C model is useful for researchers to enhance the safety of online transactions in multi-agent environments, especially if the researchers explore more components; in fact the R-D-C model is capable of adding these new components and selects the most trustworthy provider agent